Effect of Chromium Doping on Visible Light Absorption of Nanosized Titania Sol-Gel - Martínez-Ortega, F.; Pedraza-Avella, J.A.; López, R.; Páez-Mozo, E.A.; Gómez, Ricardo (Journal of nano research, 2009)
Visible light absorption of TiO2 can be induced by the addition of transition metal impurities. However, many dissimilar results have been reported about this subject and there are various interpretations about the origin of these absorption features. In this work, samples of chromium-doped titania (TiO2-Cr) with different dopant contents (0.1, 0.5, 1.0 and 5.0 wt. %) were prepared by a sol-gel method. Their particle size was determined by dynamic light scattering and it was on the nanometer scale (18 nm). X-ray powder diffraction and Raman spectroscopy showed only the presence of anatase phase in all samples. X-ray photoelectron spectroscopy reveals that the oxidation state of chromium in the prepared materials is different than in the dopant precursor. This change can be associated to the oxidative gelling conditions used in the materials preparation. UV VIS diffuse reflectance spectroscopy showed that the chromium doping, until 1.0 wt. %, did not effectively narrow the TiO2 band-gap but it induces the visible light absorption probably through the formation of color centers.